PENGEMBANGAN MEDIA GAME EDUKASI KIMIA BERBASIS ANDROID PADA SUB MATERI TATA NAMA SENYAWA HIDROKARBON DI KELAS XI SMA N 1 HULU KUANTAN - Cicin Masrita; Edi Kurniawan; Dwi Putri Musdansi (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This study aims to test the feasibility of developing an android-based chemical educational game media for nomenclature of hydrocarbon compounds. In this study using validators, namely material experts, media experts and students. This type of research is R&D development research (Research and Development) with the development process referring to the 4D development model. The data collection instrument used in the form of a validation sheet which has 5 rating scales, namely (1) not good (2) not good (3) quite good (4) good and (5) very good. The data analysis technique used is by calculating the percentage score of the validation assessment. The results showed that the percentage of material experts was 96.11% valid category, the percentage of media experts was 88.51% valid category and students showed a percentage of 91.63% valid category. Based on this assessment, an android-based chemical educational game for nomenclature of hydrocarbon compounds is very feasible to use.